The lost battles : Leanardo, michelangelo and the artistic duel that defined the renaissance - Jones, Jonathan (London : Simon & Schuster, 2010)
A riveting re-creation of the moment when Michelangelo and Leonardo went head-to-head to compete for a commission in sixteenth-century Florence: and i